Mesquite (Prosopis alba) flour as a novel ingredient for obtaining a "panettone-like" bread. Applicability of part-baking technology - Bigne, Facundo (2018)
Mesquite flour is obtained by grinding the pods of Prosopis spp., a leguminous tree widely distributed in several American countries. This flour contains valuable nutritional and functional components (minerals, fiber) that can contribute to food enrichment. In the present work, mesquite flour (MF) (150?350 g/kg) was blended with wheat flour (WF) (850-650 g/kg) to obtain composite sweet breads. The replacement with MF diminished the resilience (up to 33%) and increased the adhesiveness (up to 20%) of doughs. Higher values of dynamic moduli were obtained when MF level in composite dough was increased. Consequently, leavening was hindered by the presence of MF and thus lower maximum volumes were attained. Concomitantly, when comparing to the bread without MF, lower heights (up to 41% less) and firmer crumbs (up to 60%) were obtained after baking. Crumb microstructure showed smaller and more irregular alveoli with thicker walls when mesquite flour was added.However, sensory analysis revealed a good degree of acceptability for these composite breads, particularly at 250 g/kg replacement level. Part-baking technology was successfully used in formulations with MF since after eight weeks of frozen storage (−18 °C) no changes were observed in the texture parameters of breads in comparison with non-frozen bread.